2011
DOI: 10.1093/heapol/czr009
|View full text |Cite
|
Sign up to set email alerts
|

Opt-out HIV testing during antenatal care: experiences of pregnant women in rural Uganda

Abstract: Two years after the introduction of provider-initiated, opt-out HIV counselling and testing during antenatal care (ANC) in Uganda, HIV testing uptake is still low. This study was carried out to explore pregnant women's experiences of, and views on, the policies for opt-out, and couple HIV testing, and to understand how the policy implementation could be improved in order to increase access to prevention of mother-to-child-transmission (PMTCT) services. The study was conducted at three ANC health facilities at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 26 publications
7
80
1
Order By: Relevance
“…37 In our review, evidence from four studies, the majority involving small groups of pregnant women, indicated that patients were not always aware they had the right to decline HTC in antenatal clinics, perhaps because of the power balance between patients and health-care providers. 29,31 However, studies in other regions suggest that women may find the routine offer of HTC acceptable because it "normalizes" the process of HTC. 38 Our review has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In our review, evidence from four studies, the majority involving small groups of pregnant women, indicated that patients were not always aware they had the right to decline HTC in antenatal clinics, perhaps because of the power balance between patients and health-care providers. 29,31 However, studies in other regions suggest that women may find the routine offer of HTC acceptable because it "normalizes" the process of HTC. 38 Our review has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Women that had been offered HTC in an ANC and accepted the offer (i) 22.2% stated that refusing the offer of a test was an option and believed that women could still receive services if they opted out of testing; (ii) the majority who underwent HIV testing stated they were not given the option of refusing in the ANC; (iii) HTC was considered a precondition for receiving care Larsson, 2011 29 …”
Section: Malawimentioning
confidence: 99%
“…The importance of family support for women living with HIV can never be overestimated especially when husbands and mothers-in-law in particular have traditionally played key roles in the care and maintenance of expectant mothers. As studies have highlighted, there exists huge potential for improving the effectiveness of PMTCT programs when people living with HIV have the support of their families [13,17,[28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…While male involvement is key to couples' testing and can provide important benefits, Larsson et al (2012) highlighted significant challenges for implementation of couples' testing. The pressures on relationships arising from testing can be serious: "Women who test for HIV without their partner's knowledge or consent and turn out to be HIV positive have difficulty disclosing and face a number of potential negative reactions from their partners, including blame, and abandonment" (Medley, Mugerwa, Kennedy, & Sweat, 2012, p. 361).…”
Section: Background: Couples' Hiv Testing During Anc In Amurumentioning
confidence: 99%